THE PROCESS OF WORKING ON CANTILENA PIECES IN THE RUBAB CLASS - Abdullayev Shohruh Berdimurodovich (Web of Journals Publishing, 2025)
This article presents a detailed methodological and pedagogical analysis of working with cantilena-style pieces in the rubab class. It discusses the artistic and expressive potential of the instrument, outlines key stages of work, and emphasizes the importance of developing phrasing, legato technique, musical breathing, and performance culture in students. Practical methods, analysis of expressive tools, and guidance for repertoire selection are also included.
Keywords: Rubab, cantilena, phrasing, legato, musical breathing, expression, performance technique, pedagogy.